2005
DOI: 10.1093/ajcn/81.3.570
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in fasting leptin and insulin concentrations after acute energy restriction and subsequent compensation in food intake

Abstract: Background:The decrease in leptin after energy restriction is a starvation signal to the brain. Several studies have found an association between this decrease and subjective appetite; however, no solid data are available on the acute decrease in fasting leptin concentration and subsequent caloric compensation. Objective: The objective was to assess the effect of acute decreases in fasting leptin concentrations, induced by energy restriction, on subsequent energy intake compensation. We hypothesized that men w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 39 publications
7
44
1
2
Order By: Relevance
“…Previous studies have reported that lean individuals do not accurately adjust energy intake in response to a dietary-induced energy deficit (15,17,26,27). Consistent with the current study, either no compensation (26) or only partial compensation (15,17,27) in the 1-4 d after an acute (24-to 48-h) period of severe or complete energy restriction has been reported.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have reported that lean individuals do not accurately adjust energy intake in response to a dietary-induced energy deficit (15,17,26,27). Consistent with the current study, either no compensation (26) or only partial compensation (15,17,27) in the 1-4 d after an acute (24-to 48-h) period of severe or complete energy restriction has been reported.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings have been shown after short-term energy restriction. In the two days after 48 h on a restricted diet consisting of 38% of their estimated maintenance energy requirements and resulting in a 1.1 kg weight loss, lean young men ate 143% and 124% of their estimated energy requirements each day, respectively (Mars et al, 2005). Even in overweight people, losing weight by severely restricting energy intake increases measures of appetite such as hunger, desire to eat and estimates of prospective consumption (Mars et al, 2005 andHukshorn et al, 2003b).…”
Section: Effects Of Energy Deficit On Appetite In Humansmentioning
confidence: 99%
“…In the two days after 48 h on a restricted diet consisting of 38% of their estimated maintenance energy requirements and resulting in a 1.1 kg weight loss, lean young men ate 143% and 124% of their estimated energy requirements each day, respectively (Mars et al, 2005). Even in overweight people, losing weight by severely restricting energy intake increases measures of appetite such as hunger, desire to eat and estimates of prospective consumption (Mars et al, 2005 andHukshorn et al, 2003b). While it is often assumed that hunger is only a problem associated with very low energy diets or 'crash dieting', or with energy restriction in lean individuals, significant increases in appetite or hunger have also been measured in obese people losing weight by mild energy restriction, or by mild energy restriction combined with physical activity (Doucet et al, 2000 andWesterterp-Plantenga et al, 2001).…”
Section: Effects Of Energy Deficit On Appetite In Humansmentioning
confidence: 99%
“…Intermittent periods of OF (e.g., holiday weight gain) are often compensated by subsequent self-imposed CR, 22,23 whereas periods of CR are likely to be followed by excessive energy intake (e.g., yo-yo dieting). 23,24 Thus, the purpose of the present study was an intra-individual comparison of the effects of consecutive, controlled 1-week periods of altered energy balance (i.e., CR followed by RF, and OF followed by CR) on IS and insulin secretion in a group of healthy lean men.…”
Section: Introductionmentioning
confidence: 99%